2010
DOI: 10.1016/j.polymdegradstab.2010.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental weathering on flexural creep behavior of long fiber-reinforced thermoplastic composites

Abstract: a b s t r a c tFlexural creep behavior of nylon 6/6 (NY66)e and polypropylene (PP)e based long fiber (l/d ¼ 2000À10 000) thermoplastic (LFT) composites was investigated as a function of ultraviolet irradiation and moisture absorption. Extrusion/compression-molded panels were prepared according to ASTM D-2990 and conditioned according to ASTM D-618. NY66 and PP LFTs were characterized using scanning electron microscopy (SEM), differential scanning calorimetry (DSC), and Fourier-transform infrared (FTIR) spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 27 publications
3
43
0
Order By: Relevance
“…More recently, thermoplastic composites have found utilizaet al, 2011;Rezende et al, 2011;Chevali et al, 2010;Bates et al, 2009;Arici, 2007;Espert et al, 2004;Lee et al, 1993). A wide range of high performance thermoplastic matrices studied and reported.…”
Section: High Performance Thermoplastic Composites For Aerospace Applmentioning
confidence: 99%
“…More recently, thermoplastic composites have found utilizaet al, 2011;Rezende et al, 2011;Chevali et al, 2010;Bates et al, 2009;Arici, 2007;Espert et al, 2004;Lee et al, 1993). A wide range of high performance thermoplastic matrices studied and reported.…”
Section: High Performance Thermoplastic Composites For Aerospace Applmentioning
confidence: 99%
“…Figure 4 shows typical progressive surface colour change and degradation observed on the weathered samples' surfaces. Yellowing or discolouration is a common phenomenon observed during weathering of polymers [3].…”
Section: Discolouration Due To Weatheringmentioning
confidence: 99%
“…Ultraviolet degradation, such as photo-oxidation. This involves the formation of micro cracks and a yellowing effect on composites [2] or surface cracking on long fiber-reinforced thermoplastic composites samples [3]; 3. Hydrolytic degradation, which can cause subsequent discolouration of the material [4]; 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in terms of durability and maintenance, studies have shown that plastic lumber provides a better performance than wood lumber (WINANDY;STARK;CLEMONS, 2004;GARCÍA et al, 2009;AZWA et al, 2013;NDIAYE;GUEYE;DIOP, 2013;WEI et al, 2013) and are also economically advantageous in the long term, as their maintenance can be performed less regularly and using simple products, such as soap and water. Plastic-based products also absorb less water (STARK, 2005;CHEVALI;DEAN;JANOWSKI, 2010;KORDKHEILI, 2011;BENTHIEN;THOEMEN, 2012;LEU et al, 2012;AZWA et al, 2013;CHAVOOSHI et al, 2014;YOUSSEF;EL-GENDY;KAMEL, 2015), which contributes to a longer useful life, as effects such as swelling (KLYOSOV, 2007), component buckling (KLYOSOV, 2007), decrease in mechanical strength (STARK, 2006;STRÖMBERG;KARLSSON, 2009;MORRELL et al, 2010;KORDKHEILI, 2011) and biological degradation (STRÖMBERG; KARLSSON, 2009;HEMMATI;GARMABI, 2012;NAUMANN;STEPHAN;NOLL, 2012;AZWA et al, 2013) are minimized. However, can they really substitute wood lumber products?…”
Section: Introductionmentioning
confidence: 99%